2017
DOI: 10.1177/0731684417718385
|View full text |Cite
|
Sign up to set email alerts
|

A review on the polymeric laminates reinforced with natural fibers

Abstract: The use of composites in industries has become inevitable due to the enhancement in properties, reduction in the manufacturing cost and suitability to several applications. Among the different classifications, polymeric composites are majorly focused for their use as structural components. In a polymeric composite, the selection and composition of reinforcement play a vital role in deciding the characteristics of the composite. Although composites are developed with man-made reinforcement in the beginning stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 77 publications
0
29
0
Order By: Relevance
“…In detail, for the sisal fibers considered in this work, the experimental evidence has shown that the maximum strength is achieved by using a fiber length of about 3-4 mm; such a result is in a good accordance with ref. [34]. In order to overcame this drawback, in addition to the "short fiber" configuration, a "discontinuous fiber" configuration (with fibers longer than the critical length) obtained by using special Chopped Strand Mat (MAT) fabrics, has been also considered in the present work.…”
Section: Optimal Manufacturing Processmentioning
confidence: 99%
See 2 more Smart Citations
“…In detail, for the sisal fibers considered in this work, the experimental evidence has shown that the maximum strength is achieved by using a fiber length of about 3-4 mm; such a result is in a good accordance with ref. [34]. In order to overcame this drawback, in addition to the "short fiber" configuration, a "discontinuous fiber" configuration (with fibers longer than the critical length) obtained by using special Chopped Strand Mat (MAT) fabrics, has been also considered in the present work.…”
Section: Optimal Manufacturing Processmentioning
confidence: 99%
“…In summary, as it can be observed from the various review articles on biocomposites reported in literature [34][35][36][37][38][39][40], the use of short agave fibers for the reinforcement of thermosetting matrices (epoxy, polyester, phenolic resin etc. ), thermoplastic matrices (polyethylene, polystyrene, PVC, PLA etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 If the test is conducted using block-on-ring setup, then the specific wear rate is calculated using the model presented in equation 3. 22 The friction coefficient is measured using equation (4). where k denotes the specific wear rate (m 3 /J), Dm denotes the loss in the mass during the test (g), L denotes the length of travel (m), F n denotes the normal load applied (N), a denotes the apparent area of contact (m 2 ), Dh denotes the reduction in thickness due to wear (m), n denotes the number of engagement and disengagement, I denotes the moment of inertia of the tester considering the spindle and configuration inertia (kg m 2 ), o denotes the angular speed of the tester (rad/s), l and W denote the length and width of the wear scratch, r denotes the radius of the ring, m denotes the coefficient of friction, F denotes the frictional force against the motion (N), and R denotes the reaction offered against the applied load (N).…”
Section: Influence Of Process Parameters On Tribologymentioning
confidence: 99%
“…As a result, these natural fibre-reinforced composites enhance the possibility of biodegradability and reusability. 3,4 When a new composite is developed for structural usage, it needs to be tested for all its mechanical strengths [5][6][7][8] and during assembly of components it also requires some kind of machining to finish the surfaces, edges and corners. [9][10][11][12] If the same is used as a material where there are more friction, wear and tear, then the tribological analysis comes in to play to assess the ability of the material to resist the friction and wear.…”
Section: Introductionmentioning
confidence: 99%